Analisis Perilaku Konsumen Terhadap Pembelian Produk Mie Instan Indomie - Soraya Widitasari; Dedi Mulyadi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Data from the Word Instant Noodles Association (WINA) as of 11 May 2021 shows that Indonesia is in second place on the list of countries that consume the most instant noodles in the world. This can affect consumer satisfaction, therefore the quality of this product must be maintained in order to provide satisfaction for consumers. However, it is not only quality that must be considered. Interest in buying Indomie instant noodles for consumers must be considered, especially from the taste of these instant noodle products. The purpose of this study is to analyze consumers' purchase of instant noodles and find out the consumer's response to these instant noodle products. The problem in this research is to analyze consumer behavior towards purchasing Indomie instant noodle products. This research method in making articles uses the quantitative method according to Sugiyono (2017: 8) is a research method based on the philosophy of positivism, used to research on certain populations or samples, data collection uses research instruments, data analysis is quantitative or statistical, with the aim of test the established hypothesis.